Función jurisdiccional de la Superintendencia Nacional de Salud - Tovar Reyes, Sandra Lucía (2023)
This paper seeks to explain the jurisdiction of Colombia’s National Health Authority (Superintendencia Nacional de Salud) in conciliation and principally in judicial issues, in accordance with current regulations and relevant case law. Matters relating to the constitutionality of such powers are discus sed, along with the subjects over which this entity was given authority, the procedure or process to be followed, and the means of contesting orders from the National Health Authority that are issued as part of this process.